Baseline Assessment of Marine Litter and Microplastic Ingestion by Cold-Water Coral Reef Benthos at the East Mingulay Marine Protected Area (Sea of the Hebrides, Western Scotland) - La Beur, Laura; Henry, Lea-Anne; Kazanidis, Georgios; Hennige, Sebastian; McDonald, Alison; Shaver, Michael P.; Roberts, J. Murray (Frontiers in Marine Science, 2019)
The extent of marine litter and microplastic occurrence across ocean biomes and species remains poorly characterised, particularly in remote deep-water ecosystems. The present study in the East Mingulay Special Area of Conservation (a Marine Protected Area in the Sea of the Hebrides, western Scotland) used historic surveys and benthic samples to obtain baseline levels of anthropogenic debris and microparticle ingestion. Most debris identified in the MPA was fisheries related. A total of 11% of benthic macrofauna from Mingulay Reef Area 1 and Banana Reef had ingested microplastics, with no statistically significant effect of feeding guild, station, or reef, on ingestion rates. However, ingestion rate was highest at a station located in a topographic hollow along a gentle sloping area with strong variable ocean currents where fine-scale interactions between bathymetry and hydrography may have helped trap and focus microparticles. Raman spectroscopy of microparticles revealed several types of polymers being ingested, tentatively identified as polypropylene (PP), polyurethane (PU), polystyrene (PS), and polyethylene terephthalate (PET). Besides establishing a baseline assessment of marine litter and microparticles in a deep-water setting, the approach demonstrates the utility of using historic data and specimens collected for other purposes to expand the geographic and ecosystem coverage for larger more regional-scale and even basin-wide assessments such as those needed to inform Good Environmental Status in European waters as called for by the Marine Strategy Framework Directive.